2009
DOI: 10.5194/acp-9-8719-2009
|View full text |Cite
|
Sign up to set email alerts
|

Explicit calculation of indirect global warming potentials for halons using atmospheric models

Abstract: Abstract. The concept of Global Warming Potentials (GWPs) has been extensively used in policy consideration as a relative index for comparing the climate impact of an emitted greenhouse gas (GHG), relative to carbon dioxide with equal mass emissions. Ozone depletion due to emission of chlorinated or brominated halocarbons leads to cooling of the climate system in the opposite direction to the direct warming contribution by halocarbons as GHGs. This cooling is a key indirect effect of the halocarbons on climati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The larger CF 3 I ODPs for tropical emissions can be explained by the rapid vertical transport due to convective activities in equatorial regions that is more effective in the vertical transport of total halogens since the transport timescale in convection events (hours) is shorter than chemical loss or washout removal timescale. Youn et al (2009) showed that the differences between time variations of Halon perturbations and ozone changes, simulated by both the 2-D and 3-D models, were found not to give significantly different values for both the direct and indirect GWPs. Trace gas changes in perturbed model atmosphere for the calculation of ODP are determined with two steady-state (perturbed and baseline) model atmospheres for each scenario so that the limitation of the 2-D model mostly related to zonally-asymmetric features such as tropospheric circulation and stratospheric ozone hole does not signify in this study of evaluating potential impacts on global ozone using the two simulations.…”
Section: Key Findings and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…The larger CF 3 I ODPs for tropical emissions can be explained by the rapid vertical transport due to convective activities in equatorial regions that is more effective in the vertical transport of total halogens since the transport timescale in convection events (hours) is shorter than chemical loss or washout removal timescale. Youn et al (2009) showed that the differences between time variations of Halon perturbations and ozone changes, simulated by both the 2-D and 3-D models, were found not to give significantly different values for both the direct and indirect GWPs. Trace gas changes in perturbed model atmosphere for the calculation of ODP are determined with two steady-state (perturbed and baseline) model atmospheres for each scenario so that the limitation of the 2-D model mostly related to zonally-asymmetric features such as tropospheric circulation and stratospheric ozone hole does not signify in this study of evaluating potential impacts on global ozone using the two simulations.…”
Section: Key Findings and Conclusionmentioning
confidence: 99%
“…However, the 2-D model runs in this study of evaluating the impact of VSL compounds on atmospheric ozone were conducted in more detailed integration with a time step of 20 min due to extremely short lifetimes of the source and product gases although the above-mentioned limitations exist. The 2-D model still has the advantage of being much more computationally efficient compared to 3-D models, and thus can provide a quick reference to the slower 3-D simulations (Youn et al, 2009). …”
Section: Modeling Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier versions of the UIUC RTM have been used in previous research (e.g., Jain et al, 2000;Naik et al, 2000;Youn et al, 2009;Patten et al, 2011). The UIUC RTM calculates the flux of solar and terrestrial radiation across the tropopause.…”
Section: Model Descriptionmentioning
confidence: 99%